The Relationship of Working Hours, Incentives, and Work Environment with Work Stress on Indonesian Doctor Internship Participants Batch November 2024 in Bali Province - Komang Bram Krisna Nendra; Kusuma Anggyta; Naiem Rezki; Salsabila Chintya (Green Publisher Indonesia, 2025)
Work stress has become a common issue experienced by workers and can have negative impacts on productivity and mental health. The aim of this study is to determine the relationship between working hours, incentives, and work environments with work stress. The research was conducted on participants of the Indonesian medical internship program from the November 2024 batch in Bali Province. The type of research used is quantitative with a cross-sectional study design, and sample selection was done using purposive sampling. Data collection was carried out using a questionnaire that had been tested for validity and reliability. The data of 104 respondents were analyzed. Data analysis was conducted using One-Way ANOVA, Kruskal-Wallis, and Pearson tests. The results showed a significant positive relationship between working hours (p = 0.015) and work stress, meaning that the longer the working hours, the higher the level of work stress. There was also a significant negative relationship between the work environment (p = 0.001) and work stress, indicating that a conducive work environment can reduce the level of work stress. There was no significant relationship between incentives (p = 0.674) and work stress. These findings highlight the important role of management in creating sound policies to support the well-being of medical interns.